ETIKA SOSIAL GUS DUR - Abdus Salam (UIN Sunan Kalijaga Yogyakarta, 2014)
Islam as a complete religion that actually provides a view and the right way oflife. Yet in the reality Muslim often ignores to see social problems that continue to occur. This is seen from the lack of attention in Islam on the problem of poverty and oppression. Islam only appears in the form of individual mistake that escapist. Whereas, the Qur'an has clearly explained the concern very beautiful, as in QS. al-Baqarah [2]: 177. Therefore, it is important to re-read the meaning oflslam by more open and critical approach, one of them through discourse ethics, which in Islam is known as